Comparison of the Concept of Property Rights in the Civil Code and the Basic Agrarian Law No. 5 Year 1960 - Dermina Dalimunthe; Sawaluddin Siregar; Mulyadi Nasution (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
Authority is all things that are able to cover the essential needs of every human being, which can be obtained from other persons. The idea of eigendom in civil law is the authority to freely grasp the benefits of each good and act freely over the goods in total, provided that they are in accordance with different regulations, public order and the authority of different persons. But in agrarian eigendom appears as a regenerational, solidest and most complete authority but limited by the role of society. This research uses a qualitative descriptive method with the type of library research data collection. The legal materials obtained are classified and analyzed by content analysis using the eigendom comparison method in private law and agrarian law. From the answer to the problem formulation, the result was obtained that both discussed extensively about eigendom, but had their own uniqueness as a consequence of the varied initial concept. The regulation of property rights in western private law is broader in scope (not only land ownership) although the regulation is not comprehensive, and the granting of authority is not balanced with obligations. In the agrarian law, property rights are regulated in detail, but the focus of eigendom on land is limited by community duties, there is a balance of obligations and authority.